Ixtisoslashtirilgan ta’lim jarayonida kognitiv yondashuvning o‘quvchilardagi iqtidorni rivojlantirish xususiyatlari (SCIENCE and SOCIETY, 2025)
This article discusses the features and significance of the cognitive approach in the development of stu- dents’ talents in the process of specialized education.